Presidential Address: Signals. - Skyrms, Brian (Philosophy of Science, 2008)
The article discusses the origin of signaling systems, which allow individuals to communicate with one another even if they don't share a common language. The author addresses the concept of an innate signaling system, which is not theoretically possible if one believes in scientist Charles Darwin's theory of evolution.